2008
DOI: 10.1215/15228517-2007-040
|View full text |Cite
|
Sign up to set email alerts
|

Caring for the brain tumor patient: Family caregiver burden and unmet needs

Abstract: The rapid onset and progression of a brain tumor, cognitive and behavioral changes, and uncertainty surrounding prognosis are issues well known to health practitioners in neuro-oncology. We studied the specific challenges that family caregivers face when caring for patients experiencing the significant neurocognitive and neurobehavioral disorders associated with brain tumors. We selected 25 family caregivers of adult brain tumor patients to represent the brain tumor illness trajectory (crisis, chronic, and ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
276
3
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 251 publications
(300 citation statements)
references
References 16 publications
9
276
3
3
Order By: Relevance
“…Studies have shown that brain cancer produces a high degree of symptom burden for patients and caregivers 36,37 , with caregivers reporting poor physical and emotional health, career sacrifices, monetary losses, and immense strain 36,37 . Currently, the provision of support and coping therapy for informal carers is lacking, and that lack in turn contributes to a worsening of their stresses 34,36,38,39 . Patients are panicked and uncomfortable with the idea of shifting the type of relationship they have with their loved ones, and they do not want to impose that type of strenuous responsibility on them.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that brain cancer produces a high degree of symptom burden for patients and caregivers 36,37 , with caregivers reporting poor physical and emotional health, career sacrifices, monetary losses, and immense strain 36,37 . Currently, the provision of support and coping therapy for informal carers is lacking, and that lack in turn contributes to a worsening of their stresses 34,36,38,39 . Patients are panicked and uncomfortable with the idea of shifting the type of relationship they have with their loved ones, and they do not want to impose that type of strenuous responsibility on them.…”
Section: Discussionmentioning
confidence: 99%
“…Descriptive studies showed that family members are required to give "extraordinary uncompensated care" for months or even years. 57,58 Janda and his research group have conducted interviews with patients and family caregivers, they named the top five unsupported tumor-specific needs reported by patients with intracranial tumors, were the physical adverse effects of the tumor and treatment, changes in their mental abilities, feeling as if they were not the same person, wanting information on the latest developments in research and treatment, and changes in their ability to work. 59 Now that more people are surviving cancer, more attention than ever is focused on the quality of life and long-term outcomes of cancer survivors.…”
Section: Present Knowledge In End Of Life Care and Quality Of Dyingmentioning
confidence: 99%
“…This variability may be related to the enrolment of individuals in different disease stages, undergoing different treatments, or having different psychological and social characteristics, both for the patient and for the caregiver. In fact, it is known that different aspects of the disease or of the treatment may imply different caregiving burdens [41] as well as different psychological or relational issues [90][91][92][93][94].…”
Section: Discussionmentioning
confidence: 99%